Cytotoxicity against fish and mammalian cell lines and endocrine activity of the mycotoxins beauvericin, deoxynivalenol and ochratoxin-A. (May 2019) - García-Herranz, V.; Valdehita, A.; Navas, J.M.; Fernández-Cruz, M.L.
Abstract: The toxicity of mycotoxins is well recognized in mammals, but their effects on fish have received less attention. Moreover, in the last years several studies have reported that some mycotoxins may act as endocrine disruptors. The aim of this study was to determine the cytotoxic effects and endocrine activities of three mycotoxins: beauvericin, deoxynivalenol and ochratoxin-A. Cytotoxicity in two fish hepatoma and one mammalian hepatoma cell lines was determined by the AlamarBlue, Neutral Red Uptake and CFDA-AM assays. For the assessment of androgenic, estrogenic and thyroidal agonistic/antagonistic effects three cell lines stably expressing luciferase as reporter gene under the control of hormone receptors were used. Results showed that both fish and mammalian cell lines were very sensitive to the mycotoxins tested. OTA was the least toxic mycotoxin and DON and BEA showed similar acute toxicity. None of the three mycotoxins tested presented agonistic effects at the receptors studied, but all of them showed strong antagonistic effect at the thyroid receptor. BEA showed a weak antagonistic effect at the androgen receptor and OTA produced a biphasic dose-response curve at the estrogen receptor. The data obtained in this work are of high interest for aquaculture industries and for regulators. Highlights: Beauvericin (BEA), deoxynivalenol (DON) and ochratoxin A (OTA) are similarly toxic to fish and mammalian cell lines. BEA, DON and OTA present antagonistic effect at the thyroid hormone receptor, DON and BEA at very low concentrations. BEA seems to exert a weak antagonistic effect at the androgen receptor. OTA is an estrogen receptor antagonist, but an agonist at concentrations which produce a very low cytotoxicity.